Effect on an eight-week core strength training on one-leg dynamic balance in male well-trained athletes - Özdal, M.; Bicer, M.; Pancar, Z. (Biology of Exercise, 2019)
BACKGROUND: To train for the majority of sports, it requires a dynamic motion. Therefore, dynamic balance is important component of sport-related activities. Core strengthening is important component in sport-related activities. It is best described and understood as a highly integrated activation of multiple segments that provides force generation, proximal stability for distal mobility, and generates interactive moments. OBJECTIVE: The effects of a core strength training (CST) program on the one-legged dynamic balance (ODB) ability were examined in well-trained male volleyball players. METHODS: The subjects (N = 26) were divided into two groups as experimental group (EG, n = 13) and control group (CG, n = 13). An eight-week CST program was implemented in the EG. The CG subjects participated in their respective sport training routine. The ODB test was measured both before (pre-test) and after (post-test) the eight weeks. RESULTS: There were no significant changes between the pre- and post-tests of CG in ODB measurements (p > 0.05). All the ODB measurements were positively affected in the subjects of the EG (p < 0.05). Besides, significances were found in all the ODB measurements between the pre- and post-tests of EG subjects (p < 0.05). CONCLUSIONS: These results show that eight-week core strength training improved the one-leg dynamic balance ability.